#Blockout2024: epitome of galvanising wave of expression freedom / Muhammad Azril Roslan and Ku Mohd Amir Aizat Ku Yusof - Roslan, Muhammad Azril; Ku Yusof, Ku Mohd Amir Aizat (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The #Blockout2024 movement represents a digital protest targeting celebrities who have remained silent on the humanitarian crisis in Gaza. Initiated after the Met Gala on May 6, 2024, the movement was catalysed by social media users who juxtaposed the event's extravagance with the dire conditions in Gaza. This movement encourages individuals to block celebrities on social media, thereby reducing their influence and the revenue they generate from advertising deals. The main goal of #Blockout2024 is to make celebrities take responsibility for not speaking up about the Gaza conflict. By blocking them on social media, activists want to reduce their visibility and affect their income from followers and ads. Thus, by encouraging celebrities to actively involve themselves in addressing the Gaza crisis, the #Blockout2024 movement aims to harness their collective influence for the greater good of humanity and global welfare.